PELATIHAN DIGITAL ENTREPRENEURSHIP UNTUK MEWUJUDKAN KEMANDIRIAN EKONOMI PADA MASA PANDEMI DI DESA SALAMKANCI - Fadhilah Rahmawati; Agnira Rekha; Megita Dwi Pamungkas (LPPM Universitas Bina Bangsa, 2021)
The purpose of this activity is to overcome the problems faced by partners, namely the lack of public awareness to utilize technology to entrepreneurship to meet economic needs during the pandemic. The emergence of the current problem is due to a lack of public knowledge related to the use of technology in entrepreneurship. People think that entrepreneurship requires a lot of capital and technology can only help businesses that have grown. With this activity, it is expected that the public has the awareness to utilize technology to start and support entrepreneurship activities for various commodities so that economic independence can be achieved and improve the welfare of the community, especially during the pandemic. The approach used in this activity is PRA (Participatory Rural Appraisal). This approach engages people to understand problems and increases the participation of the community to solve their problems. In this activity, residents represented by PKK mothers were given socialization about the use of technology for entrepreneurship in Salamkanci Village, Bandongan Subdistrict, Magelang Regency continued counseling on economic independence, then given motivation and training on the use of technology in entrepreneurship to practice training results